Bangkitnya Kaum (Islam) Abangan - Mua’allim, Amir (Unisia, 2016)
The success of PDIP in the last general election is often considered as the success of the subsistent Abangan politic. The Abangan politic becomes a popular term in line with the role of Santri politic in Indonesia political process, fnspite of the controvercy around those terms, the writer of. this book tries to analyze the development of the subsistent Abangan politic. The religion teaching of virtue and humanity should result the inclonclusive and tolerant attitude so that the attitude of destruction, assasination and violence do not represent the religion teaching. The correlation between the dominacy of Abangan politic and the heigtening violence conflict becomes the main focus on this book.